The effect of psycho-social factors on the level of burnout among the trainers of IKBN and IKTBN in Selangor - Ahmad Shah Razin, Shahril (2019)
The prevalence of burnout has become a significant issue in higher learning vocational institution in Malaysia. Past studies found that high risk of burnout among employee is due to high exposure to emotionally demanding work. The main characteristic of burnout is emotional exhaustion that can present among the trainers in Institut Kemahiran Belia Negara (IKBN) and Institut Kemahiran Tinggi Belia Negara (IKTBN). As such a cross-sectional study was conducted to investigate the level of burnout and the relationship between job demand, job stress and social support with burnout among the trainers of IKBN and IKTBN in Selangor. This study was applying the quantitative method by distributing questionnaires consisting of 77 items comprising instruments measuring burnout, job demand, job stress and social support to the 119 respondents from IKTBN Sepang, IKTBN Dusun Tua, IKBN Kuala Langat, and IKBN Peretak. The result shows that there is a low level of burnout among the trainers in IKBN and IKTBN Selangor. Furthermore, there is a significant relationship between job demand and job stress with burnout. However, there is no significant relationship between social support and burnout. As such, to control the effect of job demand and job stress, this study proposes for the implementation of Total Wellness and Health Promotion (TWHP), as it can provide a more holistic approach to the trainers. By educating and providing resources, the trainers can self-sufficiently able to control the effect of job demand and job stress to mitigate burnout.